Imaging and pathological comparison of inflammatory pseudotumor-like follicular dendritic cell sarcoma of the spleen: A case report and literature review - Chen, Fuxing; Li, Junqiang; Xie, Pingkun (Frontiers in Surgery, 2022)
Background Inflammatory pseudotumor-like follicular dendritic cell sarcoma (IPT-like FDCS) is a rare subtype of follicular dendritic cell sarcoma (FDCS) that is mainly located in the liver and spleen (1). Splenic IPT-like FDCS is a rare low-grade malignancy with non-specific clinical manifestations and laboratory findings. Herein, we reported the pathological and imaging features of a case with splenic IPT-like FDCS. Case presentation A 57-year-old woman was found to have a mass in the spleen during a physical examination and was hospitalized for further treatment. Her laboratory results were within the normal range. Unenhanced and contrast-enhanced computed tomography scans of the whole abdomen showed a round mass in the spleen, with a diameter of about 5 cm. After further examination with enhanced MRI, a provisional diagnosis of splenic hemangioma or splenic hamartoma was made. The patient underwent splenectomy, and the pathological diagnosis was splenic IPT-like FDCS. No tumor recurrence or metastasis was found during the 1-year follow-up after the operation. Conclusions Herein, we reported a case of splenic IPT-like FDCS. Although the clinical examination and laboratory examination lack specificity, the imaging of this case showed that the lesion was a solid mass with progressive enhancement, and the central scar showed the characteristics of delayed enhancement, which facilitated the diagnosis.